Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3390/environments3020010
|View full text |Cite
|
Sign up to set email alerts
|

Relating Water Quality and Age in Drinking Water Distribution Systems Using Self-Organising Maps

Abstract: Understanding and managing water quality in drinking water distribution system is essential for public health and wellbeing, but is challenging due to the number and complexity of interacting physical, chemical and biological processes occurring within vast, deteriorating pipe networks. In this paper we explore the application of Self Organising Map techniques to derive such understanding from international data sets, demonstrating how multivariate, non-linear techniques can be used to identify relationships t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…These ordered, colour contour maps enable the researcher to visually identify similar patterns between some of them; this would mean that similar levels of different variables typically matched over time. That is, the visual inspection of the component planes of the SOM provides a rapid and intuitive means of examining the covariance between the selected variables in order to obtain an increased understanding of the system [26], especially in complex problems with several potential variables involved (e.g., [27]). Based on the conclusions of these first steps, a more in-depth analysis could be performed, and a simple prediction model was developed.…”
Section: Discussionmentioning
confidence: 99%
“…These ordered, colour contour maps enable the researcher to visually identify similar patterns between some of them; this would mean that similar levels of different variables typically matched over time. That is, the visual inspection of the component planes of the SOM provides a rapid and intuitive means of examining the covariance between the selected variables in order to obtain an increased understanding of the system [26], especially in complex problems with several potential variables involved (e.g., [27]). Based on the conclusions of these first steps, a more in-depth analysis could be performed, and a simple prediction model was developed.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters were chosen for multiple reasons. For example, changes in residual chlorine are linked with pollution by chemicals like ammonia and biofilm growth; chlorine reactions with corrosion products and COD could most likely explain low residual chlorine levels at the end of the network, where water age can be high [21]. The low residual chlorine levels in the Mukono reservoir and areas that follow are more likely due to this reason.…”
Section: Choice Of Water Quality Parametersmentioning
confidence: 99%
“…Higher turbidity levels are often associated with higher levels of viruses, parasites and some bacteria [22]. There can be correlations between water age and chlorine levels [21]. Exposure to extreme pH values results in irritation to the eyes, skin, and mucous membranes [23].…”
Section: Choice Of Water Quality Parametersmentioning
confidence: 99%
“…This type of modelling has provided insight into the self-cleaning effect and shown that the self-cleaning velocity that has to be reached at 50 % of the days is 0.20 to 0.25 m s −1 in the tertiary network (Blokker et al, 2010b(Blokker et al, , 2011cSchaap and Blokker, 2011). With SIMDEUM, a better prediction of the residence time will be available, and the study of the relation between the residence time and the water quality may also improve Blokker et al, 2016).…”
Section: Research In the Dwdsmentioning
confidence: 99%